2021
DOI: 10.1111/jomf.12746
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Separation Parenting Time Schedules in Joint Physical Custody Arrangements

Abstract: Objective The objective of the study was to examine patterns of parenting time schedules in joint physical custody (JPC) arrangements. Background Although the importance of contact with the non‐residential parent for children's well‐being after family dissolution is well‐documented, the measures used in surveys are often crude and do not capture the two dimensions of post‐separation parenting time schedules: the proportion of time children spend with each parent and the number of transitions children make betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…However, it must always be submitted to the Family and Minors Court for approval or hearing, if necessary, except family circumstances in which it is not possible or when it is not in the best interests of the child. Notwithstanding this, household arrangements remain asymmetric as in other western countries [33,39]. Even with equivalent groups of sole and joint psychical custody, the distribution of the number of days with fewer days spent with the father follows that found in earlier studies Based on attachment to the mothers, children under three are traditionally in sole custody, spending fewer overnights with the father, thus overlooking attachment to fathers or father involvement [14,55].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, it must always be submitted to the Family and Minors Court for approval or hearing, if necessary, except family circumstances in which it is not possible or when it is not in the best interests of the child. Notwithstanding this, household arrangements remain asymmetric as in other western countries [33,39]. Even with equivalent groups of sole and joint psychical custody, the distribution of the number of days with fewer days spent with the father follows that found in earlier studies Based on attachment to the mothers, children under three are traditionally in sole custody, spending fewer overnights with the father, thus overlooking attachment to fathers or father involvement [14,55].…”
Section: Discussionmentioning
confidence: 76%
“…Even in joint physical custody, asymmetric care arrangements and overnights are more frequent. The quality of interparental relationship and the parents' working hours was found to positively predict symmetric joint physical custody plans [33]. Some studies found equal levels of well-being in children from both types of child physical custody, similar to those from non-separated families [17,31,34] or sole vs. joint physical custody, emphasizing the role of low parental psychopathology and high parenting and coparenting [35].…”
Section: Child Physical Custodymentioning
confidence: 99%
See 1 more Smart Citation
“…Children living in SPC arrangements spent less than 30% with either their mother or their father (with the other parent being the residential parent), and children living in JPC arrangements spent between 30% and 50% of their time with both their mother and their father. We did not differentiate between days and nights but calculated the total amount of time that the child spent with either parent (see also Steinbach & Augustijn, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have attributed this relationship to the additional costs that are associated with practicing joint physical custody (Cancian et al, 2014;Poortman & van Gaalen, 2017), including the costs of maintaining two suitable homes and having two sets of furniture, clothes, and toys for the children (Bakker & Mulder, 2013). Moreover, because there is some evidence that joint physical custody is associated with frequent transitions between the parents' households (Steinbach & Augustijn, 2021), this care arrangement may also involve higher travel costs (Vanassche et al, 2017), especially when the parents live far away from each other.…”
Section: Theoretical Considerations On the Relationship Between Joint...mentioning
confidence: 99%